Intra-procedural monitoring protocol using routine transthoracic echocardiography with backup trans-oesophageal probe in transcatheter aortic valve replacement: a single centre experience. (11th April 2019) - Stella, S; Melillo, F; Capogrosso, C; Fisicaro, A; Ancona, F; Latib, A; Montorfano, M; Colombo, A; Alfieri, O; Castiglioni, A; Margonato, A; Agricola, E
Abstract: Aim: The aim of this study is to describe our 9-year experience in transcatheter aortic valve replacement (TAVR) using transthoracic echocardiography (TTE) as a routine intra-procedural imaging modality with trans-oesophageal echocardiography (TEE) as a backup. Methods and results: From January 2008 to December 2017, 1218 patients underwent transfemoral TAVR at our Institution. Except the first 20 cases, all procedures have been performed under conscious sedation, with fluoroscopic guidance and TTE imaging monitoring. Once the TTE resulted suboptimal for final result assessment or a complication was either suspected or identified on TTE, TEE evaluation was promptly performed under general anaesthesia. Only 24 (1.9%) cases required a switch to TEE: 6 cases for suboptimal TTE prosthetic valve leak (PVL) quantification; 12 cases for haemodynamic instability; 2 cases for pericardial effusion without haemodynamic instability; 4 cases for urgent TAVR. The 30-days and 1-year all-cause mortality were 2.1% and 10.2%, respectively. Cardiac mortality at 30-days and 1-year follow-up were 0.6% and 4.1%, respectively. Intra-procedural and pre-discharge TT evaluation showed good agreement for PVL quantification (k agreement: 0.827, P  = 0.005). Conclusion: TTE monitoring seems a reasonable imaging tool for TAVR intra-procedural monitoring without delay in diagnosis of complications and a reliable paravalvular leak assessment. However, TEE is undoubtedly essential in identifying the exact mechanism in most of the complications.